2012
DOI: 10.1080/07399332.2011.645963
|View full text |Cite
|
Sign up to set email alerts
|

Muslim Women's Physician Preference: Beyond Obstetrics and Gynecology

Abstract: When Emirati (Muslim) women (n = 218) were asked about their preferred physician (in terms of gender, religion, and nationality) for three personal clinical scenarios, a female was almost exclusively preferred for the gynecological (96.8%) and "stomach" (94.5%) scenarios, while ±46% of the women also preferred a female physician for the facial allergy scenario. Only 17% considered physician gender important for the prepubertal child scenario. Just over half of the women preferred a Muslim physician for persona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
24
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 43 publications
(142 reference statements)
3
24
1
1
Order By: Relevance
“…In general, the more traditional and religious beliefs, the greater importance patients attached to the gender preference of their provider, due to modesty. This was previously verified by several gender preference studies that explored gender preference of religious and traditional women for their obstetrician/gynecologist physician (Amer-Alshiek et al, 2015;Amir, Hazan, Grutz, Amit, & Azem, 2012;Amir, Tibi, et al, 2012;Lafta, 2006;McLean et al, 2012;Rizk, El-Zubeir, Al-Dhaheri, Al-Mansouri, & Al-Jenaibi, 2005). The marital status of the responders might also link to a more modest behavior of married patients.…”
Section: Discussionmentioning
confidence: 67%
“…In general, the more traditional and religious beliefs, the greater importance patients attached to the gender preference of their provider, due to modesty. This was previously verified by several gender preference studies that explored gender preference of religious and traditional women for their obstetrician/gynecologist physician (Amer-Alshiek et al, 2015;Amir, Hazan, Grutz, Amit, & Azem, 2012;Amir, Tibi, et al, 2012;Lafta, 2006;McLean et al, 2012;Rizk, El-Zubeir, Al-Dhaheri, Al-Mansouri, & Al-Jenaibi, 2005). The marital status of the responders might also link to a more modest behavior of married patients.…”
Section: Discussionmentioning
confidence: 67%
“…Studies have shown that 35-57 % of female patients prefer female OB/GYNs [36,37] and furthermore these patients are more satisfied if treated by female OB/GYNs [38]. This gets even more obvious if religious aspects are taken into account (e.g., Muslim patients [39]). Therefore, we have to be aware that any imbalances regarding the gender distribution amongst providers in OB/GYN could also have an impact on care and satisfaction of patients.…”
Section: Discussionmentioning
confidence: 97%
“…of their time or expertise, or if services are delivered in a way deemed unsatisfactory to the population they intend to serve (Whitehead, 1992). Equity in health service delivery encompasses accommodation of cultural preferences, such as Muslim women's preference for a female physician (McLean et al, 2012), and provision of services such as language interpretation to facilitate communication between health care professionals and patients (Gagnon, 2004).…”
Section: Equity In Access To Health Care Servicesmentioning
confidence: 99%